Multiple phytohormones and phytoalexins are involved in disease resistance to Magnaporthe oryzae invaded from roots in rice. Issue 3 (12th May 2014) - Duan, Liu; Liu, Hongbo; Li, Xianghua; Xiao, Jinghua; Wang, Shiping
<x xml:space="preserve">Abstract</x> Blast, caused by the fungus Magnaporthe oryzae, is one of the most devastating diseases of rice worldwide. Phenylalanine ammonia lyase (PAL) is a key enzyme in the phenylpropanoid pathway, which leads to the biosynthesis of defense‐related phytohormone salicylic acid (SA) and flavonoid‐type phytoalexins sakuranetin and naringenin. However, the roles and biochemical features of individual rice PALs in defense responses to pathogens remain unclear. Here, we report that rice OsPAL06, which can catalyze the formation of trans‐cinnamate using l‐phenylalanine, is involved in rice root–M. oryzae interaction. OsPAL06‐knockout mutant showed increased susceptibility to M. oryzae invaded from roots and developed typical leaf blast symptoms, accompanied by nearly complete disappearance of sakuranetin and naringenin and a two‐third reduction of the SA level in roots. This mutant also showed compensatively induced expression of chalcone synthase, which is involved in flavonoid biosynthesis, isochorismate synthase 1, which is putatively involved in SA synthesis via another pathway, reduced jasmonate content and increased ethylene content. These results suggest that OsPAL06 is a positive regulator in preventing M. oryzae infection from roots. It may regulate defense by promoting both phytoalexin accumulation and SA signaling that synergistically and antagonistically interacts with jasmonate‐ and ethylene‐dependent signaling, respectively.